Ionic versus Nonionic Paramagnetic Contrast Media in Differentiating between Postoperative Scar and Recurrent Disk - Hsu, Jui-Sheng; Liu, Gin-Chung; Chen, Shih-Hsien; Jaw, Twei-Shiun; Shen, Wun-Jer; Chen, Chiao-Yun (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: In theory, ionic solutes diffuse more slowly in cartilage than do nonionic solutes. We tested the hypothesis that the contrast ratio between scar and recurrent disk fragment on MR images is greater after IV administration of an ionic rather than a nonionic contrast medium when a clinical dose is used.METHODS: Twenty patients who had recurrent lumbar disk herniation were enrolled in this study. The enhancement of epidural scar and recurrent disk fragment was measured at 5, 25, 40, and 50 min after IV injection of ionic and nonionic contrast media (0.1 mmol/kg)RESULTS: The enhancement was consistently and significantly higher for scar than for recurrent disk fragment, although the contrast ratio between scar and recurrent disk fragment decreased between 5 and 50 min after the administration of each contrast medium. No significant difference was shown between ionic and nonionic contrast media in the enhancement of recurrent disk fragment at 5, 25, 40, and 50 min after injection. The contrast ratio between scar and recurrent disk fragment was not a significant difference at 5, 25, and 40 min after administration of both contrast media. At 50 min, the contrast ratio between scar and recurrent disk fragment was 1.32 ± 0.41 with ionic contrast medium and 1.20 ± 0.56 with nonionic contrast medium. The difference was significant.CONCLUSION: The contrast ratio between scar and recurrent disk fragment is affected by the timing of the imaging. Images obtained immediately after the injection of each contrast medium showed a greater contrast ratio than did delayed images. In addition, with the ionic medium, this difference was greater than with nonionic medium at 5, 25, 40, and 50 min after injection and that difference reached statistical significance at 50 min.